Analisis Uji Kompetensi Wartawan PWI Jawa Timur untuk Meningkatkan Profesionalitas (Jurnal Kajian Media, 2017)
This study aims to analyze what measures Indonesian Press Council - East Java branch takes to improve its members' professionalism through UKW. This study uses a descriptive qualitative research approach using case-study method to answer the problem formulation. The result of this study shows that there is a correlation between UKW and professionalism of journalists who have taken the test. Although in its implementation, improvement and evaluation should continually be performed to acquire higher quality results. However, UKW might at least be a "damper" for journalists for not violating journalistic ethical codes. This has been proven in the last five years. Indeed, PWI-East Java branch has rarely received complaints from citizens on violation by its members. Keywords: Journalist Competency Test, Professionalism, Press Freedom.